How to Make the Ghosts in my Bedroom Disappear? Focused-Attention Meditation Combined with Muscle Relaxation (MR Therapy)—A Direct Treatment Intervention for Sleep Paralysis - Jalal, Baland (Frontiers in Psychology, 2016)
Sleep paralysis (SP) is a common state of involuntary immobility occurring at sleep onset or offset. It can include terrifying hypnogogic or hypnopompic hallucinations of menacing bedroom intruders. Unsurprisingly, the experience is associated with great fear and horror worldwide. To date, there exist no direct treatment intervention for SP. In this article, I propose for the first time a type of focused inward-attention meditation combined with muscle relaxation as a direct intervention to be applied during the attack, to ameliorate and possibly eliminate it (what could be called, meditation-relaxation or MR therapy for SP). The intervention includes four steps: (1) reappraisal of the meaning of the attack; (2) psychological and emotional distancing; (3) inward focused-attention meditation; (4) muscle relaxation. The intervention promotes attentional shift away from unpleasant external and internal stimuli (i.e., terrifying hallucinations and bodily paralysis sensations) unto an emotionally pleasant internal object (e.g., a positive memory). It may facilitate a relaxed meditate state characterized by a shift from sympathetic to parasympathetic dominance, associated with greater levels of alpha activity (which may lead to drowsiness and potentially sleep). The procedure may also reduce the initial panic and arousal that occur when realizing one is paralyzed. In addition, I present a novel Panic-Hallucination (PH) Model of Sleep Paralysis; describing how through escalating cycles of fear and panic-like autonomic arousal a positive feedback loop is created that worsens the attack (e.g., leading to longer and more fearful episodes), drives content of hallucinations, and causes future episodes of SP. Case examples are presented to illustrate the feasibility of MR therapy for SP.